Features of assessment of enterprise investment attractiveness in market conditions - Yessengeldin, B.S.; Kantureev, M.Т.; Zhakhmetova, A.K. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with the market mechanisms of investment attractiveness development of the enterprise in modern conditions. The authors summarize various interpretations of the concept of «investment attractiveness of the enterprise», defined requirements for enterprises to invest depending on the risk and profitability. The article analyzes the invested investment resources in fixed assets by the size of enterprises of the Republic of Kazakhstan. The authors determine the possibility of obtaining maximum profit as a result of capital investment in small businesses with a minimum risk of investment. The article focuses on investments in fixed assets in the sectors of the economy of the Republic of Kazakhstan. It is noted that the efficiency of investment determines the investment attractiveness which is the investment activity of the enterprise. The authors classify the methods of investment attractiveness assessment by the following groups: methods based on the definition of financial indicators of the enterprise; methods based on the definition of production capacity, quality management, evaluation of the external environment; methods based on indicators of attractiveness of shares; methods of complex estimates; methods of comparative rating estimates; methods of cost estimates. The authors note that in order to determine the level of investment attractiveness, statistical and expert information is required, on the basis of which single or complex evaluation criteria are formed. Recommendations on the assessment of investment attractiveness are suggested as an object of management for the owners and management of the enterprise.